2021
DOI: 10.1093/zoolinnean/zlab070
|View full text |Cite
|
Sign up to set email alerts
|

Integrative taxonomy of West African Magelona (Annelida: Magelonidae): species with thoracic pigmentation

Abstract: Benthic samples collected during several cruises from shelf areas along the West African coast from Morocco to Angola, have highlighted a huge diversity of magelonid species (over 20 species), many of which are undescribed. The majority of samples were taken as part of two large-scale projects in the region: the Canary Current Large Marine Ecosystem project (CCLME) and the Guinea Current Large Marine Ecosystem project (GCLME). Six magelonid species bearing posterior thoracic pigmentation have been highlighted,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Additionally, a recent study based on anatomical and ecological observations of Magelona species proposed that the terms commonly identified as peristomium and proboscis in other polychaeta taxa should be replaced with "achaetous first segment" and "burrowing organ", respectively, to better align with their specific functions [5,24]. In addressing this issue, the morphological criteria and standardized terms proposed by renowned taxonomic specialists in Magelona, Mortimer et al [13,24,25] and Parapar et al [2], may be highly effective in clearing up existing confusion. Notably, their emphasis on the comprehensive illustration and detailed description of all thoracic chaetigers in taxonomic treatments stands out as a crucial contribution.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a recent study based on anatomical and ecological observations of Magelona species proposed that the terms commonly identified as peristomium and proboscis in other polychaeta taxa should be replaced with "achaetous first segment" and "burrowing organ", respectively, to better align with their specific functions [5,24]. In addressing this issue, the morphological criteria and standardized terms proposed by renowned taxonomic specialists in Magelona, Mortimer et al [13,24,25] and Parapar et al [2], may be highly effective in clearing up existing confusion. Notably, their emphasis on the comprehensive illustration and detailed description of all thoracic chaetigers in taxonomic treatments stands out as a crucial contribution.…”
Section: Discussionmentioning
confidence: 99%
“…The Magelonidae is a small family of marine annelids, consisting of 81 extant species within the genus Magelona F. Müller, 1858 (Mortimer and Mackie, 2006; Mortimer et al ., 2021a, 2021b). Magelonid worms are recorded in most of the world's regions and the Temperate Northern Atlantic is one of the most diverse in terms of the number of known magelonid species, which could be partially attributed to geographic bias of taxonomic work in the region.…”
Section: Introductionmentioning
confidence: 99%
“…Even with the magnitude of records available for these species, habitat descriptions are often based largely on information from the original descriptions, despite several uncertainties. For example, information on the type locality for M. alleni was not clearly defined by Wilson (1958), the sediment type was based upon visual judgement alone, being noted as abundant in black sandy mud off Rame Head, which Mortimer et al (2021b) concluded to be approximately 60 m deep. The type locality of M. minuta was simply described as shelly mud with a small amount of sand (Eliason, 1962).…”
Section: Introductionmentioning
confidence: 99%